Effect of multibanded magnetic field on convective heat transport in linearly heated porous systems filled with hybrid nanofluid - Manna, Nirmal K.; Mondal, Chitrak; Biswas, Nirmalendu; Sarkar, U. K.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal H. (Aip Publishing, 2021)
The paper attempts to enhance the control of convective transport phenomena in magnetothermal devices applying a technique of multibanded magnetic field. For this demonstration, a typical cavity-like thermal system is considered involving linear heating, porous substance, hybrid nanofluid, and magnetic field. Four identical bands of magnetic fields are applied horizontally with uniform inactive zones between the bands. The transport equations of the coupled multiphysics evolving from the thermal buoyancy (due to linear heating at one sidewall and isothermal cooling at the opposite sidewall), filled porous medium, spatially intermittently active magnetic fields, and the engineered working fluid of Cu-Al2O3/water hybrid nanofluid are solved by an indigenously developed computing code. The study is conducted using the pertinent dimensionless parameters for the following ranges: Darcy-Rayleigh number (Ra-m=1-10(4)), Darcy number (Da=10(-5) - 10(-1)), Hartmann number (Ha=0-70), and concentration of hybrid nanoparticles phi (= 0-2%). The convective phenomena are analyzed using the heatlines (for heat transport), streamlines (flow pattern), isotherms (static temperature), and the average Nusselt number (for heat transfer). The outcomes of this technique of multibanded magnetic field are rigorously compared with other established application methods of magnetic fields. It establishes different local behaviors along with an improved heat transfer. Heatline visualization reveals the definite portraits of heat flow paths depending upon parametric values. Furthermore, the presence of linear heating is in particular treated to explore the insight of linear heating (that featuring multiple heating and cooling zones along with the linear heater), utilizing the local Nusselt number and heatlines. One of the important advantages of this new technique is it is more energy-efficient particularly for the square or shallow cavity. The multibanded magnetic field shows a promising technique for the control of convective transport phenomena involving coupled multiphysics used during sophisticated applications (such as materials processing, biomedical applications, etc.).
Keywords: Mhd Natural-Convection; Turbulence Intensity Distribution; Entropy Generation; Mixed Convection; Square Cavity; Thermomagnetic Convection; Numerical-Simulation; Meniscus Flow; Enclosure; Visualization